Total direct cost of managing maxillofacial trauma and related injuries caused by motor vehicle accidents in hospital universiti sains malaysia, kubang kerian, kelantan. - Chiew Fong, Mary Chok (2011)
Introduction: Maxillofacial trauma due to motor vehicle accidents had increased the clinical burden of health care institutions. Economic evaluation on the management of maxillofacial trauma had been studied in many countries. Information related to the factors associated with the cost of managing maxillofacial trauma is worth explored. Objectives: The objectives of this study were to determine the total direct medical cost of managing maxillofacial trauma caused by motor vehicle accidents and the associated factors. Patients and Methods: This was a cross-sectional study of 73 participants treated for maxillofacial trauma due to motor vehicle accidents at Hospital Universiti Sains Malaysia from 1st January 2010 to 31st December 2010. The outcome variable was total direct medical cost consisted of the sum of macro-cost and micro-cost. The association between total direct medical cost and study factors (socio-demographic factors, mode of injury and clinical characteristics) were analyzed using general linear regression. Box-Cox transformation was used to transform total direct medical cost in the regression analysis. Results: The median total direct medical cost was RM5,899.51 and ranged from RM82 to RM1.5 million. The average cost per-person was RM58,398.20. The cost consisted 97.3 and 2.7 percent of macro-cost and micro-cost respectively. Factors significantly associated with the transformed total direct medical cost were the length of stay in hospital (regression coefficient 0.08, 95% confidence interval 0.03, 0.12; P=0.001), number of facial soft tissue injury (regression coefficient -1.08, 95% confidence interval -1.78, -0.38; P=0.003) and number of maxillofacial fracture (regression coefficient 1.64, 95% confidence interval 0.44, 2.84; P=0.008). Length of stay was found interacted with other significant factors. The cost associated with length of stay was different in each number of maxillofacial fracture and soft tissue injury. Conclusion: In conclusion, length of stay in hospital, number of maxillofacial fracture and number of facial soft tissue injury were significantly associated with total direct medical cost of managing maxillofacial trauma caused by motor vehicle accident.